KINERJA KARYAWAN DILIHAT DARI PENERAPAN NILAI-NILAI ISLAMI, GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI - Purnomo, Wahyu Agung Adji; Fatimah, Feti; Rusdiyanto, Rusdiyanto (Growth, 2023)
The development of the business world in the current era is increasing rapidly, both in the industrial and service sectors. In fact, the existence of the sharia industry in the last decade has been increasingly widespread in various parts of the world, and is also developing in countries with a Muslim minority population. The tourism industry is of course very closely related to the accommodation business, especially the sharia hotel business, especially sharia hotels, which is one of the business sectors that offers good profits, because now modern people who go out of town for work or just for vacation really need lodging or hotel services. In this research was conducted to influence the influence of the application of Islamic values, leadership style, and organizational culture on employee performance. This study uses multiple linear regression testing. The population used is Seven Dream Syari'ah Hotel and Resto employees. As for sampling with non-probability sampling method as many as 35 respondents. The results of the partial test (t test) show that the application of Islamic values, leadership style, and organizational culture has a positive and significant effect on the performance of Seven Dream Syari'ah Hotel and Resto employees.